Postal in the Abbasid State - عمران رشا; وفاء صارم; شيرين حمودي (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The breadth and diversity of the Abbasid Caliphate and the large number of its internal and external problems played a major role in the expansion of bureaus that reached a great degree of progress in the Abbasid era. The post office was one of the most important weapons of the Abbasids in achieving the political goals that they set themselves up to achieve, and through it they knew the secrets of those who rebelled against their authority and resisted revolutions and eliminated many movements and retained their authority and influence ,and they took care of arranging it and appointing trustworthy people to manage it and transmit the news .Therefor the postal owner enjoyed a great prestige with the Caliph and the Abbasid Caliphate. Permanent Keywords: postage, funerals, hoodies, ALwalaq , ALfaraniq, ALiaskdar